Focus Marking Strategies In Igbo - Amaechi, Mary; Georgi, Doreen (My University, 2022)
In this paper we describe the encoding of term focus in the Benue-Kwa language Igbo. Next to a discussion of focus marking devices that are available in the language and their different pragmatic usage conditions, we highlight the fact that the observed subject/non-subject split in focus encoding provides novel insights into the scope and generality of the focus marking generalization put forward in Fiedler et al. (2010). We argue that the distribution of focus markers is not solely regulated by pragmatic principles (viz. to avoid a default topic interpretation especially for subjects), but also by the syntactic position of the focus marker, its morphological realization conditions as well as a ban on too local subject movement.
Keywords: Focus marking; Igbo; West African Languages